Strengthening character and citizenship education: a case study of teaching materials in elementary schools - Atna Tiningrum; Anggraini, Ade Eka; Dewi, Radeni Sukma Indra; Arifin, Slamet (Jurnal Bidang Pendidikan Dasar, 2025)
The fading character of politeness and cooperation among elementary school students encourages the need for innovation in teaching materials. This research focuses on Canva and Heyzine-based digital teaching materials to strengthen character and citizenship education at SDN Pisangcandi 3. The aim is to analyze the effectiveness of teaching materials in improving students' character values. The case study method was used with data collection techniques through observation, interviews, document analysis, and questionnaires. Thematic analysis was conducted in three stages: data reduction, data presentation, and conclusion drawing. The results showed an increase in students' understanding of the value of politeness and cooperation through interactive and interesting digital teaching materials. However, there are challenges in optimization related to teacher skills and resource availability. In conclusion, the innovation of digital teaching materials is effective in shaping student character, with recommendations for teacher training for further effectiveness.